Dominican Republic - South-South Cooperation in Action : Responding to Avian Influenza - Ekanayake, Indira Janaki; Rabin-Solomon, Bari; Balcet, Jean Claude (World Bank, Washington, DC, 2012)
The Low Pathogenic Avian Influenza (LPAI) H5N2 virus was detected in the Dominican Republic (DR) late last year, causing a serious disruption in sub-regional trade, poultry production, and food security. In collaboration with the World Bank, the DR Secretariat of state for agriculture organized a workshop to share regional knowledge on preparedness for emergency actions to deal with avian flu. This note captures interesting themes from the workshop.